Services and manufacturing in global value chains: Is the distinction obsolete? - Sébastien Miroudot (Asian Development Bank Institute (ADBI), 2019)
Many studies discuss the "de-industrialization" or "servicification" of economies in both developed and developing countries. Such studies rely on statistics that distinguish a manufacturing from a service sector. But in the age of global value chains (GVCs), it becomes increasingly difficult to disentangle manufacturing from service activities. Goods are produced with services, services are produced with goods, some manufacturing firms are factory-less, and companies tend to sell solutions to customers by bundling goods with services. This business reality has important implications for trade and industry analysis. Against this backdrop, the paper introduces a taxonomy of service activities in GVCs and describes the main statistical challenges in assessing the contribution of manufacturing and services to output, value added, or trade. It then reviews three approaches that take GVCs into account in the analysis of income, comparative advantage, and productivity to address these challenges. As statisticians are working on improving the framework for understanding global production, policymakers should be aware of the blurring lines between goods and services.
Keywords: F14; F23; F68; L60; L80; 330